2016
DOI: 10.14218/jcth.2016.00012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Granulocyte Colony-Stimulating Factor on Patients with Liver Failure: a Meta-Analysis

Abstract: Background and Aims: It remains controversial whether granulocyte colony-stimulating factor (G-CSF) prolongs survival in liver failure (LF) patients. This meta-analysis was performed to evaluate the effect of G-CSF on patients with LF.Methods: PubMed, EMBASE, and Web of Science databases were searched to identify English language randomized controlled trials comparing G-CSF with control therapy published before14 February 2015. A meta-analysis was performed to examine changes in liver function and patient surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It is unclear whether these differences can be explained by ethnic differences or different liver failure causes. Moreover, different diagnostic criteria for ACLF caused different patient prognosis ( 20 ). We need more RCTs and high-quality literature are required to clarify the usefulness of G-CSF for ACLF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether these differences can be explained by ethnic differences or different liver failure causes. Moreover, different diagnostic criteria for ACLF caused different patient prognosis ( 20 ). We need more RCTs and high-quality literature are required to clarify the usefulness of G-CSF for ACLF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…**p \ 0.01; ***p \ 0.001 compared to MSC:SC 0.1 tissues and organs, we generated MSC cell lines expressing G-CSF and IGF-1. Several reports have shown the potential therapeutic use of G-CSF in regenerative medicine, including cardiac (Harada et al 2005;Ieishi et al 2007;Macambira et al 2009), neurological (Huang and Tsai 2014;Guo et al 2015) and hepatic diseases (Yang et al 2016). The immunomodulatory potential of G-CSF suggests that transgenic MSC expressing this growth factor may also contribute to the modulation of inflammation at the site of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…GCSF prevented sepsis events). 50 The mechanism of action of GCSF in amelioration or prevention of sepsis in advanced cirrhosis is not yet elucidated. However, in the study by Fiuza et al, 51 GCSF was found to improve and increase recruitment of neutrophils to sites of infection and to enhance neutrophil transendothelial migration in cirrhotic patients in the absence of neutrophil adhesion, which could be one of the reasons underlying the beneficial action of GCSF in sepsis.…”
Section: Critical Appraisal Of Gcsf In Decompensated Cirrhosismentioning
confidence: 99%
“…The authors concluded that the GCSF-treated ACLF patients had significantly reduced short-term mortality with limited evidence. Another metanalysis by Yang et al 50 included five studies with mostly 3 months follow-up in patients with ACLF. Those authors concluded that GCSF treatment in patients with advanced liver failure significantly improved liver function, reduced the incidence of sepsis, and prolonged short-term survival.…”
Section: Critical Appraisal Of Gcsf In Decompensated Cirrhosismentioning
confidence: 99%